BIOLOGY OF LADY BIRD BEETLE, CRYPTOLAEMUS MONTROUZIERI (MULSANT) ON COTTON MEALY BUG, PHENACOCCUS SOLENOPSIS (TINSLEY) - M. R. SIDDHAPARA; S. G. DUMANIYA; M. B. PATEL; N. V. PATEL (The Bioscan, 2013)
Investigation on biology of Cryptolaemus montrouzieri (Mulsant) on cotton mealy bug, Phenacoccus solenopsis (Tinsley) revealed that it did not lay eggs in the mealy bug colonies under the laboratory conditions when reared on P. solenopsis. However, the eggs were laid on the surface of pink hibiscus flowers. The eggs were spindle shaped and pale yellow in colour. The average incubation period and hatching percentage were 5.12 ± 0.87 days and 92.61 ± 3.93 per cents, respectively. The larvae passed through four instars. The average developmental period of first, second, third and fourth instar larva was 3.04 ± 0.28, 2.34 ± 0.48, 3.06 ± 0.24 and 4.18 ± 0.48 days, respectively. The average total larval period was 12.62 ± 1.67 days, while prepupal and pupal period were 1.88 ± 0.39 and 6.98 ± 0.58 days, respectively. The average pre-oviposition, oviposition and post-oviposition period were 5.68 ± 1.10, 41.04 ± 2.26 and 5.26 ± 1.21 days, respectively. The average fecundity of the female was 303.76 ± 17.22 eggs. The average longevity of male and female was 42.32 ± 2.03 and 51.98 ± 2.68 days, respectively. Total life cycle occupied on an average of 68.92 ± 2.37 days by male and 78.58 ± 2.98 days by female. The sizes of various stages of C. montrouzieri were also recorded.